Pedagogia e educação não escolar no Brasil: crítica epistemológica, formativa e profissional - Severo, José Leonardo Rolim de Lima (2015)
This study consisted of an investigative approach about initial teacher education for professional interventions in Non School Education spaces (NSE). Its development was guided by the following structural questions: how NSE is constituted as formation object in Pedagogy course? Which epistemological meanings attributed to Pedagogy do inform the curriculum of pedagogue education program? Which professional knowledges and abilities the Pedagogy course does need to achieve in order to educate the pedagogue to acting in located educational practices in the NSE contexts? These questions summarize the problematization mode of this study object in which it is sought to understand how the NSE is constituted as pedagogue education object for certain epistemological meanings attributed to Pedagogy embodied in those curricular documents. Based on this general objective, the study was guided by the objectives of mapping ways to insert NSE in the curriculum of Pedagogy course in Brazil; identifying the way in which Pedagogy, as scientific field, is meant in these documents; understanding the relationship between the configuration mode of NSE and the epistemological meaning of Pedagogy; and discussing the relationship between professional knowledges and abilities of non-formal educational practice in the perspective of educators that work in NSE spaces. From a constructionist epistemological point of view, it is chosen the use of a mixed methodological scheme operated in two phases: 1) content analysis of 20 curriculum of pedagogue education programs in Brazil; 2) data analysis of 38 virtual questionnaire answered by teachers who work or have worked in NSE spaces in several regions of Brazil on the relationship between pedagogue education knowledge and challenges of pedagogical practice in this area. The research results indicate that, as was analyzed in curricular documents, the NSE content in the curriculum of pedagogue education program is characterized by dispersion, abundance, lack of specificity, disarticulation with respect to the general framework of the objectives and curricular organization of Pedagogy and it is barely contemplated by disciplines and formative axes/dimensions. In contrast, the approach of professional knowledges and abilities from the data collected with teachers, unfolds the demand of participating in socialization experiences and building knowledge that outline a more organic formation profile during initial pedagogue education marked by a broad concept of teaching profession. The epistemological reframing of Pedagogy, as Science of Education, set up a way of coping with such a problem, because it allows a more consistent understanding of the base and the object of the curriculum from which one can see more clearly the theoretical and methodological field where they are located.